Trois petits traités ludiques de fiction. - Catherine Tauveron (Strenae, 2011)
This article studies the workings and scope of three picture books (Chester by Mélanie Watt, My Cat, The Silliest Cat in the World, by Gilles Bachelet, and Les mammouths, les Ogres, les extraterrestres et ma petite sœur by Alex Cousseau and Nathalie Choux) which works to represent metaleptic leaps in scenes in a waterfall effect, as well as characters who’re either unaware of their alienation or, on the contrary, lucid about their precarious ontological state, thus presenting themselves as hilarious little treatises on fiction. They ask fundamental questions (What is a fictional being? What is an author? What relationship do they have?) and in so doing, they have a "sobering effect" on young readers by breaking the usual reading pact. At the same time, they produce an "intoxication effect” on the reader—that of entering the mysterious little factory of literature and finding oneself as close as possible to the character's torments, sympathizing with their wild dreams, their existential discomforts, their frustrations, and their delusions of selfhood.